Shallow groundwater level time series and groundwater chemistry survey data from Krycklan catchment - Erdbrügger, Jana; van Meerveld, Ilja; Seibert, Jan; Bishop, Kevin (GFZ Data Services, 2022)
Abstract Groundwater can respond quickly to precipitation and is the main contribution to streamflow in most catchments in humid, temperate climates. To better understand shallow groundwater dynamics in a boreal headwater catchment, we installed a network of groundwater wells in two areas in the Krycklan catchment in Northern Sweden. This dataset contains groundwater level data and sampling data from a small headwater catchment (3.5 ha, 54 wells) and a hillslope (1 ha, 21 wells). The dataset is arranged in to subsets, Dataset 1 and 2, the first containing groundwater levels and related information while the second contains information on the chemical sampling procedure and laboratory results. The average wells depth was 274 cm (range: 70 - 581 cm) and recorded the groundwater level variation at a 10-30 min interval between 18. July 2018 – 1. November 2020. Manual water level measurements (0 - 26 per well) during the summer seasons in 2018 and 2019 were used to confirm and re-calibrate the water level logger results. The groundwater level data for each well was carefully processed and quality controlled, using six data labels. The location and depths of the wells are in the file 2022-020_Erdbruegger-et-al_Krycklan_gw_wells.csv and the groundwater levels and classifications 2022-020_Erdbruegger-et-al_Krycklan_gw_levels.csv. The absolute and relative positions of the wells were measured with a high-precision GPS and terrestrial laser scanner (TLS) to determine differences in groundwater levels and thus groundwater gradients (the report of the registration of the point clouds can be found in the files 2022-020_Erdbruegger-et-al_TSL_registration_report_[A/B].rtf). During the summer of 2019, all wells with sufficient water were sampled and analyzed for electrical conductivity, pH, absorbance, anion and cation concentrations, as well as δ18O and δ2H (information on the sampling and the laboratory results can be found in the files 2022-020_Erdbruegger-et-al_Krycklan_gw_chemistry.csv, ...